Tantangan Kode Etik Guru di Era Globalisasi di Sekolah SMA Prayatna Medan - Nasution, Abdul Fattah; Tahara, Ananda; Sukmawan, Indah; Akbar, Tuah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The teacher's code of ethics is a set of moral norms and principles that must be upheld by a teacher in carrying out his duties as an educator. The concept of learning that focuses on developing students' character and morals makes the teacher's code of ethics even more important to implement. This study aims to understand the concept of a teacher's code of ethics and how this code of ethics can be integrated into character learning. The research method used is literature study by collecting information from various sources such as journals, books, and related documents. The results of the study show that the teacher's code of ethics includes moral principles such as honesty, integrity, responsibility, and respect. This code of ethics can be applied in character learning by integrating it into learning programs, building good relationships with students, and demonstrating behavior that is consistent with espoused moral values. Therefore, teachers must understand the applicable code of ethics and develop the ability to apply it in character learning.